2018
DOI: 10.1080/17425247.2018.1504017
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in oral delivery of biologics: nanomedicine and physical modes of delivery

Abstract: Research into oral delivery of biologics has a long and rich history but has not produced technologies used in the clinic. The area has evolved in terms of strategies to promote oral biologics delivery from early chemical absorption enhancers to nanomedicine to devices. Continued activity in this area is justifiable considering the remarkable proliferation of biologics. Areas covered: The article discusses some physiological barriers to oral delivery of biologics, with a special focus on less characterized bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 108 publications
0
34
0
Order By: Relevance
“…In the field of drug delivery, while the drug barrier functions of mucus and epithelium are relatively well-characterized, the filter function of the BM is seldom studied [10][11][12]. But currently, there is a growing interest to understand the barrier function of the BM due to advances in the mucosal delivery of complex therapeutics such as macromolecules and nanomedicines [12,13]. The diffusion of macromolecules through the BM of non-keratinized oral mucosal epithelium was initially studied by Alfano et al, who observed that the BM restricts the penetration of smaller macromolecules (inulin, 5 kDa), while allowing easy passage of larger macromolecules (Dextran, 20 kDa) [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of drug delivery, while the drug barrier functions of mucus and epithelium are relatively well-characterized, the filter function of the BM is seldom studied [10][11][12]. But currently, there is a growing interest to understand the barrier function of the BM due to advances in the mucosal delivery of complex therapeutics such as macromolecules and nanomedicines [12,13]. The diffusion of macromolecules through the BM of non-keratinized oral mucosal epithelium was initially studied by Alfano et al, who observed that the BM restricts the penetration of smaller macromolecules (inulin, 5 kDa), while allowing easy passage of larger macromolecules (Dextran, 20 kDa) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several formulation strategies have emerged for the delivery of proteins orally ( Table 3 ). The use of protease inhibitors to dampen proteolytic enzyme activity, and permeation enhancers [ 105 , 236 , 237 ], ultrasound [ 238 , 239 ], microjet systems [ 238 , 240 ] and microneedle capsules [ 238 , 241 ] to improve drug absorption have recently been explored as techniques to maintain the bioactivity of the administered proteins as well as enhance transport through disrupted tight junctions [ 105 ]. These formulations are capable of remaining intact throughout transit and allow for drug absorption into the systemic circulation.…”
Section: Polypeptide Deliverymentioning
confidence: 99%
“…Patches are relatively novel systems for oral delivery of small and macromolecules with mucoadhesive properties [ 242 ]. Similar to a transdermal patch, intestinal patches are able to encapsulate and protect the desired drug while adhering to the intestinal wall [ 238 , 242 ], thus positioning the drug at the desired absorption site [ 241 ]. A patch consists of three layers: a mucoadhesive material, a drug-loaded layer and a relatively impermeable drug-protecting membrane [ 242 ].…”
Section: Polypeptide Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of macromolecule and nanomedicine drug delivery, the molecular barrier is extensively researched with the view of achieving non-invasive delivery of the therapeutics [3,44] and the understanding of some of the component barriers of the mucosae has helped in developing effective drug delivery strategies against these barriers [45]. However, the barrier function of BM in drug delivery studies is a field that is not fully appreciated.…”
Section: Importance Of the Basement Membrane In Drug Deliverymentioning
confidence: 99%